2018
DOI: 10.1038/s41598-018-35868-5
|View full text |Cite|
|
Sign up to set email alerts
|

In silico discovery of a FOXM1 driven embryonal signaling pathway in therapy resistant neuroblastoma tumors

Abstract: Chemotherapy resistance is responsible for high mortality rates in neuroblastoma. MYCN, an oncogenic driver in neuroblastoma, controls pluripotency genes including LIN28B. We hypothesized that enhanced embryonic stem cell (ESC) gene regulatory programs could mark tumors with high pluripotency capacity and subsequently increased risk for therapy failure. An ESC miRNA signature was established based on publicly available data. In addition, an ESC mRNA signature was generated including the 500 protein coding gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 65 publications
0
12
0
Order By: Relevance
“…The development of therapy resistance is another complex NB issue in which the functions of miRs have been realized. Differential expression of miRs in association with NB clinicobiological physiognomies and their functions in disease pathogenesis have been noted [50,51]. For instance, a unique embryonic stem cell miR signature in NB and its association with high-risk disease and poor prognosis were reported [52].…”
Section: Targeting Mirnasmentioning
confidence: 99%
“…The development of therapy resistance is another complex NB issue in which the functions of miRs have been realized. Differential expression of miRs in association with NB clinicobiological physiognomies and their functions in disease pathogenesis have been noted [50,51]. For instance, a unique embryonic stem cell miR signature in NB and its association with high-risk disease and poor prognosis were reported [52].…”
Section: Targeting Mirnasmentioning
confidence: 99%
“…Although this focus is still in its infancy, researchers are attempting to understand the basics. On that note, with an in silico approach, studies have listed a panel of ESC miRs along with mRNA signatures that are associated with poor NB patient outcomes, specifically for the N-MYC-amplified and N-MYC non-amplified high-risk subsets [171] . In addition, the findings indicated that the ESC signature is majorly driven by FOXM1 and could be useful to inhibit tumor progression and therapy resistance.…”
Section: Role Of Mirs In Nb Therapy Resistancementioning
confidence: 99%
“…This is of interest given that 17q gains and amplifications are a recurrent finding in cancers including embryonic malignancies such as neuroblastoma and medulloblastoma. In neuroblastoma, we recently reported an elevated ESC‐derived stemness gene signature activity in ultra‐high‐risk patients 7 . In view of the above, we investigated the selective growth advantage of segmental chromosomal aberrations (with primary focus on 17q+) in hESCs under controlled replicative stress conditions as this may also provide insights into the functional significance of recurrent 17q + in cancer cells.…”
Section: Introductionmentioning
confidence: 99%